Priorities for a global cassava research program to improve food security and incomes in developing countries: A survey of experts. - Rusike, Joseph; Abdoulaye, Tahirou; Kleinwechter, U.; Creamer, Bernardo; Pemsl, Diemuth E.; Kirscht, H.; Hareau, Guy (2012)
The resources available for implementing the CGIAR Research Program Roots, Tubers, and Bananas (CRP-RTB) are limited and have an opportunity cost in terms of foregone alternatives.There are many alternative research options that can be pursued to improve food security and incomes for resource-poor farmers in developing countries. This raises the need to identify how to best invest limited resources in order to generate the greatest impacts per dollar invested. The CRPRTB proposes a six stage process for setting priorities. As an initial step in this process, this study describes the perceptions of cassava research priorities by cassava researchers, development and extension specialists. These experts were asked to rank three top constraints on cassava production, transformation and commercialization and to rate the importance of 13 kinds of research options to reduce poverty and improve food security. The ranking was based on a five-point scale, between 5 as the most important and 1 as the least important research option. Results presented reflect perceptions of critical priorities for cassava research based on tallying of the response and provide the basis for further priority setting in the CRP-RTB.